Relationship between Development of Secondary Sex Characters and Androgenic Gland in Macrobrachium idella (Hilgendorf) - Cubelio, Sherine S.; D.M., Thampy (Fishery Technology, 2025)
The secondary sex characters such as length of cheliped, length of appendix masculina and number of spines on it, and the width of vas deferens are under the control of the androgenic gland and have no relationship with the body size of the prawn, Macrobrachium idella. Of the 30 individuals randomly selected, 22 had a body length to cheliped length ratio below 1:1.5. The size of the androgenic gland and appendix masculina were not fully developed in them, indicating that they are reproductively inactive. Remaining 8 individuals, having a body length to cheliped length ratio above 1:1.5, had well-developed androgenic gland and appendix masculina showing that there is positive correlation between the biomass of androgenic gland and the degree of development of secondary sex characters